(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
This mixed methods study, employing a convergent design, aimed to investigate the school climate and burnout among mathematics teachers in Davao City. The participants were identified utilizing purposive sampling. Results yielded a significant negative correlation between school climate and burnout, and faculty relations, in its singular capacity significantly predicted burnout among the mathematics teachers. Moreover, the qualitative data of this study were gathered from the participants through the in-depth interview and focus group discussion, both required the participants to answer open-ended questions. Through thematic analysis, the researchers unearthed five essential themes from the participants’ lived experiences. In totality, the nature of data integration is merging-converging. A teacher empowerment action plan was proposed based on the results and findings.